2019
DOI: 10.3889/oamjms.2019.089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Parameters of Diode Laser on Acceleration of Orthodontic Tooth Movement and Its Effect on Relapse: An Experimental Animal Study

Abstract: AIM: Recent studies have demonstrated that low-level laser therapy (LLLT) can accelerate orthodontic tooth movement. However, there is still controversy about the optimum parameters that can cause acceleration. The present study was designed to examine two different doses of LLLT in the acceleration of orthodontic tooth movement and their effect on relapse. METHODS: An orthodontic appliance was designed to induce tooth movement on lower incisors of rabbits. The in-al-as diode laser was used to radiate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Several factors affect the rate of tooth movement (Abdelhameed and Refai, 2018, Elkattan et al, 2019, Patterson et al, 2016:Makrygiannakis et al, 2018, Jiang et al, 2017, Jahanbakhshi et al, 2016). It is reasonable to assume that the effect of occlusal interferences was minimal in this study as only class II div I malocclusion cases were included.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors affect the rate of tooth movement (Abdelhameed and Refai, 2018, Elkattan et al, 2019, Patterson et al, 2016:Makrygiannakis et al, 2018, Jiang et al, 2017, Jahanbakhshi et al, 2016). It is reasonable to assume that the effect of occlusal interferences was minimal in this study as only class II div I malocclusion cases were included.…”
Section: Discussionmentioning
confidence: 99%
“…These prolonged period of retention causes patient compliance issues as well as oral hygiene problems associated with fixed and removable retainers. With adjunctive procedures such as low‐level laser therapy, we can achieve more predictable results in treating orthodontic patients (38). Animal studies regarding the effect of photobiomodulation on laser relapse can help identify ways to accelerate orthodontic treatments and maintain the clinical outcomes and increase the overall prognosis of these treatments (39).…”
Section: Discussionmentioning
confidence: 99%
“…Further clinical trials are needed to achieve even better results and more cost-effective and easily available devices and methods for decreasing the orthodontic treatment time and hence the complications associated with it. 21 In-Ga-As 250 W/cm 2 2,500-5,000 J/cm 2 940 ± 10 Yes Üretürk et al 27 Ga-Al-As 20 mW: 10 seconds/point 5 J/cm 2 /point 820 Yes Qamruddin et al 28 Ga-Al-As 100 mW: 3 seconds/point 7.5 J/cm 2 /point 940 Yes Limpanichkul et al 29 Ga-Al-As 100 mw 25 J/sq.cm 850 No Heravi et al 30 Ga-Al-As 200 mW 21.4 J/sq.cm 810 No Doshi-Mehta and Bhad-Patil 31 Ga-Al-As 100 nW 8 J/sq.cm 810 Yes Cruz et al 32 Ga-Al-As 20 mW 5 J/sq.cm 780 Yes Sousa et al 33 Ga-Al-As 20 mW 5 J/sq.cm 780 Yes Dalaie et al 34 Ga-Al-As 100 mW 5 J/sq.cm 800 No…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on animals have suggested an increased inflammatory response by increasing the mediators such as cytokines, colony-stimulating factor, interleukins, growth factors, tumor necrosis factor, etc. 11,12,15,21 The studies on humans have been done by devise-assisted methods that have shown reduction in treatment time. Bowman 17 and Orton-Gibbs et al 16 in their studies have used devise-assisted vibratory methods and found the time needed for alignment and leveling and reaching a bigger dimension archwire like 19 × 25 stainless steel or NiTi reduced by 30%.…”
Section: Mechanical and Resonance Vibrationmentioning
confidence: 99%
See 1 more Smart Citation